State of the Art: Treatment of Bipolar Disorders - Severus, Emanuel (CNS Neurosci Ther, 2011)
Bipolar disorders are lifelong lasting affective disorders, with an episodic course of the illness in most cases. The lifetime prevalence is around 2–5%, the illness usually appears in early adulthood and causes significant impairment in psychosocial functioning. This is a selective review focusing on recent developments and issues of interest in the psychopharmacological treatment of bipolar disorders. It is based primarily on the results of adequately powered, randomised, controlled trials (RCTs). These studies were systematically retrieved by means of a Medline search. The past 10 years have led to a broadening of the psychopharmacological treatment options for bipolar disorders. The proof of efficacy for the combination of fluoxetine/olanzapine as well as quetiapine in the acute treatment of bipolar I depression were important steps. While lithium remains the gold standard in the maintenance treatment of bipolar disorders, valproate, olanzapine, lamotrigine, aripiprazole, and quetiapine have been shown efficacious for this indication, with quetiapine possessing the broadest approval status of all drugs for the different treatment phases of this illness. Despite this progress there remains a huge demand regarding new compounds for nearly every area in the psychopharmacological treatment of bipolar disorders. In addition new methodological approaches regarding the proof of effectiveness in clinical practice are urgently needed.